Factors associated with the prolonged hospital stay in elderly adults - Jesus-Carbajal, Celenne L. (2019)
Introduction: the group of older adults will have the largest proportional increase in the world and with this premature loss of functional capacity that determines the days of hospitalization. Objective: to determine the association of falls, comorbidities and malnutrition as risk factors for a prolonged hospital stay in older adults. Methods: a case-control study was conducted in adults older than 60 years and more hospitalized in the period from August 1 to October 31, 2018, the sample of 84 patients who were divided into two groups, less than 6 days hospitalization (control) and those of 6 and more days (cases). The Chi square test and a bivariate inferential analysis were used. Results: of the total, the group of 75 and more represented 27.38% (which were cases) and the group of 60 to 74 years was 30.95% (of the controls). A statistically significant association was observed with comorbidities and malnutrition with an odds ratio (OR) of 1 and 1.27 (p <0.05) respectively. And also with the intermediate variables gender and marital status with RP OR of 2.17 and 1 (p <0.05). However, a statistically significant association of variable falls with prolonged hospital stay with an OR of 0.59 (p> 0.05) could not be found. Conclusion: There is no association between the variable falls, comorbidities and malnutrition, but there is an association of gender (male) and marital status (married and widowed) as risk factors for prolonged hospital stay at the EsSalud II Huánuco Hospital in 2018.